YKTT2018 Yrittäjyyskasvatuspäivät 2018 : Abstraktikirja - Oksanen, Lea; Peltonen, Kati; Laakso, Hilkka (LUT University, 2018)
The 12th annual Entrepreneurship Education Conference - YKTT2018 - by the Scientific Association for Entrepreneurship Education brings together scientists, teachers and other actors to a two-day venue at the Sibelius Hall in Lahti on October 3-4, 2018. This year the conference focuses on the following themes: strengthening, leading and managing Entrepreneurship education, Entrepreneurial culture and intrapreneurship in different contexts. The themes form an umbrella for various and multifaceted aspects enlightening the present and the future of entrepreneurship education. As in previous years, the Entrepreneurship Education Conference encourages people to come together and strengthen their networks, as well as inspires and depicts an overall picture of the current state of entrepreneurship education research and development activities in Finland. The keynote speakers of YKTT2018 are Professor Lene Foss from UiT - The Arctic University of Norway, Researcher in entrepreneurial education Martin Lackéus from the Chalmers University of Technology in Sweden and Emerita Professor Paula Kyrö. We will also hear the recent results of the assessment by the Finnish Education Evaluation Centre “Entrepreneurship and innovative capacity in higher education and vocational education and training” as well as their guidelines for development. The thematic sessions and workshops comprise altogether 36 presentations. This book of abstracts contains all the summaries of the presentations, classified thematically, in alphabetical order according to the first author. Additionally, the Federation of Finnish Enterprises organizes a workshop for actors in higher education. Furthermore, a one-day session “Entrepreneurship education in the basic and upper secondary education” targeted for teachers in the basic and upper secondary education takes place on Thursday, 4 October. During the day, teachers have an opportunity to share the ideas and best practices of entrepreneurship education. The organizers of the 12th Entrepreneurship Education ...